Pengaruh Konsentrasi NO2 Udara Ambien pada Daerah Padat Kendaraan Terhadap Konsentrasi NO2 Udara Dalam Ruang (Studi Kasus di Kawasan Simpang Pulai Kota Jambi) - Anggrika Riyanti; Peppy Herawati; Nyimas Hazana Pajriani (Universitas Batanghari Jambi, 2018)
Transportation sector has a very big influence in air pollution. Increase the number of vehicles will caused higher air pollution, such as NO2. The increase in ambient air pollution is feared to have an impact on indoor air pollution. This study purposed is to determine the relationship between NO2 concentration in ambient to indoor air. This study used kuantitatif methods with purposive sampling for one month in Simpang Pulai Jambi City. The relationship between NO2 concentration of ambient air and indoor air was analyzed using simple pearson correlation. The result showed that there was no significant relationship between NO2 concentration in ambient to indoor air with correlation value (r) is 0,437. The highest NO2 concentration found on the third week in ambient 109,139 µg/m3and indoor air 70,133 µg/m3. From analysis in one month showed that NO2 concentration in Simpang Kawat Jambi City still meet the air quality standard (150 μg / m3) in Government Regulation Number 41 Year 1999 about Air Pollution Control.